Are birds more afraid in urban parks or cemeteries? A Latin American study contrasts with results from Europe - Morelli, Federico; Leveau, Lucas M; Mikula, Peter; MacGregor-Fors, Ian; Bocelli, M Lucia; Quesada-Acuña, Sergio Gabriel; González-Lagos, César; Gutiérrez-Tapia, Pablo; Dri, Gabriela Franzoi; Delgado-V, Carlos A; Zavala, Alvaro Garitano; Campos, Jackeline; et al. (The Science of the total environment, 2023)
The escape behaviour, measured as flight initiation distance (FID; the distance at which individuals take flight when approached by a potential predator, usually a human in the study systems), is a measure widely used to study fearfulness and risk-taking in animals. Previous studies have shown significant differences in the escape behaviour of birds inhabiting cemeteries and urban parks in European cities, where birds seem to be shyer in the latter. We collected a regional dataset of the FID of birds inhabiting cemeteries and parks across Latin America in peri-urban, suburban and urban parks and cemeteries. FIDs were recorded for eighty-one bird species. Mean species-specific FIDs ranged from 1.9 to 19.7 m for species with at least two observations (fifty-seven species). Using Bayesian regression modelling and controlling for the phylogenetic relatedness of the FID among bird species and city and country, we found that, in contrast to a recent publication from Europe, birds escape earlier in cemeteries than parks in the studied Latin American cities. FIDs were also significantly shorter in urban areas than in peri-urban areas and in areas with higher human density. Our results indicate that some idiosyncratic patterns in animal fearfulness towards humans may emerge among different geographic regions, highlighting difficulties with scaling up and application of regional findings to other ecosystems and world regions. Such differences could be associated with intrinsic differences between the pool of bird species from temperate European and mostly tropical Latin American cities, characterized by different evolutionary histories, but also with differences in the historical process of urbanization.
Keywords: ptáci; Humans; Urbanization; Birds; Parks, Recreational; Phylogeny; Urban parks; veřejné parky; Escape behaviour; hřbitovy; Ecosystem; Latinská Amerika; Latin America; Human disturbance; Cemeteries; lidé; zvířata; Europe; Urban ecology; Cities; Fear-response; fylogeneze; Aves; Neotropics; Bayesova věta; Animals; velkoměsta; Bayes Theorem; Evropa; ekosystém